50 Years of Materials Research for Photocatalytic Water Splitting - Marschall, Roland (European journal of inorganic chemistry, 2021)
50 years ago, Fujishima and Honda published their work on photoelectrocatalytic water splitting with the aid of the light absorbing semiconductor TiO2. Since then, many different novel absorber materials for water splitting have been discovered and investigated. This Minireview aims to briefly summarize the most important materials developments for photocatalytic water splitting of that time, differentiating between single absorbers and Z‐schemes. This Minireview aims to briefly summarize the most important material developments for heterogeneous photocatalytic water splitting of the last 50 years, focusing on single absorbers and Z‐schemes.